Migrasi Database Dari Cds/Isis Ke Slims - Mohamad Hamim (IAIN Ponorogo, 2011)
CDS-ISIS is a library software developed by UNESCO,to help the library managers in developing countries that less budget to develop it. In accordance with the need to fast access on data and the flexible data sharing bears an idea to build library software. SLiMs—Senayan Library Management System—is Open Source Software (OSS) web based. The main purpose of SLiMs is to fulfill information system on a small or large library. The feature is very complete and users would have flexible management to the library both of intranet or internetbase. SLiMs provides features to export data from or import data to, using CSV (comma-separated values) format. The release of stable 7 version, this feature could be used to export and import bibliographic record from data source. The standard format enables Senayan database to share between other library softwares respectively as long as those applications could export on this format.